Review on Advanced Cancer Modeling for a Cancer Study - Yong-Hee Cho (Current Issues in Molecular Biology, 2022)
Intensive efforts to develop anti-cancer agents have been made for over 60 years. However, cancer is still considered a lethal disease. To study the best anti-cancer agents for improving the survival rates of cancer patients, many researchers have focused on establishing advanced experimental applications reflecting on the biomimetics of cancer patients involving the heterogeneity of cancer cells. The heterogeneity of cancer cells, which are derived from various clones and affected by different environments, presents different genetic backgrounds and molecular characteristics attributed to the differential responses to cancer therapies, and these are responsible for the resistance to cancer therapies, as well as for recurrence following cancer treatments. Therefore, the development of advanced applications for the cancer patient is expected to help the development of more effective anti-cancer agents. The present review evaluates recently developed cancer models encompassing the heterogeneity of cancer cells, which present similar morphological architecture, genetic backgrounds, and molecular characteristics to corresponding patient tumor tissues.